2015
DOI: 10.4103/2231-4040.161507
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone derivatives as potential antifungal agents: Synthesis, and antifungal activity

Abstract: Much research has been carried out with the aim to discover the therapeutic values of chalcone derivatives. Chalcones possess wide range of pharmacological activity such as antibacterial, antimalarial, antiprotozoal, antitubercular, anticancer, and antifungal agents etc. The presence of reactive α,β-unsaturated keto group in chalcones is found to be responsible for their biological activity. The rapid developments of resistance to antifungal agents, led to design, and synthesize the new antifungal agents. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 10 publications
2
44
0
Order By: Relevance
“…Since chalcones with different substituents than the ones synthesized here have shown antifungal activities in several previous papers, [51][52][53][54][55][56][57][58] the antifungal properties of these compounds could add new interesting data on the antifungal behavior of chalcones. Thus, the nine chalcones 11-19 were tested for antifungal properties against the clinically important yeasts C. albicans (ATCC 10231) and C. neoformans (ATCC 32264).…”
Section: In Vitro Antifungal Effects On Fungi Pathogenic To Humansmentioning
confidence: 78%
“…Since chalcones with different substituents than the ones synthesized here have shown antifungal activities in several previous papers, [51][52][53][54][55][56][57][58] the antifungal properties of these compounds could add new interesting data on the antifungal behavior of chalcones. Thus, the nine chalcones 11-19 were tested for antifungal properties against the clinically important yeasts C. albicans (ATCC 10231) and C. neoformans (ATCC 32264).…”
Section: In Vitro Antifungal Effects On Fungi Pathogenic To Humansmentioning
confidence: 78%
“…The results obtained showed that the tested chalcone derivatives that contain aromatic amine substituents have no antibacterial or antifungal activity against all the tested clinical pathogenic species of bacteria and fungi. Many chalcones are known to exhibit reasonable antimicrobial and antifungal activity due to the presence of α,β-unsaturated carbonyl groups that can enhance the activity 3,4. In case of chalcone derivatives (3a–c), there are more than one α,β-unsaturated carbonyl group (chalcone) substituted on one benzene ring, which leads to electronic and steric interactions between the substituents.…”
Section: Discussionmentioning
confidence: 99%
“…Chalcones are used as precursors in the biosynthesis of flavonoids and isoflavonoids. Some of them were found to have remarkable biological activities and can act as antibacterial,2 antifungal,3 antiinflammatory,4 antimalarial,5 and anticancer agents 6. The presence of α,β-unsaturated carbonyl moiety as the functional group makes the chalcones biologically active 7.…”
Section: Introductionmentioning
confidence: 99%
“…Chalcones (Figure (b)) are a well‐known class of natural products belonging to a family of flavonoid. Displaying a diverse range of therapeutically important properties as antibacterial, antiviral, anti‐fungal, anti‐inflammatory, anti‐oxidant, and anti‐tumor agents, they have attracted much of interest in the field of medicinal chemistry. Recently many studies have been carried out by introducing a slight modification into the chalcone backbone to obtain compounds with better anti‐oxidative and anti‐inflammatory activity …”
Section: Introductionmentioning
confidence: 99%